2003
DOI: 10.1023/a:1021635826032
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Turnover rates of myelin membrane components in mouse brains were determined by a method using stable isotope-labeling and mass spectrometry. The half-replacement times based on incorporation rates of newly synthesized molecules for young adult mice were 359 days for cholesterol, 20 days for phosphatidylcholine, 25 days for phosphatidylethanolamine, 94 days for cerebroside and 102 days for ganglioside GM1. The turnover rates of half-lives of myelin components were calculated from the decay curves of initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…However, a possible explanation may relate to the half life for myelin related proteins, which in animals has been determined to be in the same approximate time frame as the clinic deterioration seen in these cases of DPHLE (Figure 4; mean time for lucid interval: 19 days). A study by Ando et al 12 . found that the half-replacement times as judged by newly synthesized molecule incorporation rate in young adult mice was 20 days for phosphatidylcholine, 25 days for phosphatidylethanolamine.…”
Section: Discussionmentioning
confidence: 99%
“…However, a possible explanation may relate to the half life for myelin related proteins, which in animals has been determined to be in the same approximate time frame as the clinic deterioration seen in these cases of DPHLE (Figure 4; mean time for lucid interval: 19 days). A study by Ando et al 12 . found that the half-replacement times as judged by newly synthesized molecule incorporation rate in young adult mice was 20 days for phosphatidylcholine, 25 days for phosphatidylethanolamine.…”
Section: Discussionmentioning
confidence: 99%
“…myelin), with a half-life of ϳ1 year in mice (38). The stability of brain cholesterol is further highlighted by the fact that overall CNS cholesterol concentration is unchanged in animal models where genes known to be involved in cholesterol transport are inactivated.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, isotope labeling and mass spectrometry have been employed to overcome these pitfalls. Using a pulse of deuterated water, the half‐lives of myelin lipids were estimated to range from 360 days for cholesterol to 24 days for phosphatidylcholine (Ando, Tanaka, Toyoda, & Kon, 2003). Following an analogous approach in which proteins were pulse‐labeled with 15 N followed by a chase period with 14 N, the myelin proteins myelin basic protein (MBP), proteolipid protein (PLP), myelin oligodendrocyte glycoprotein (MOG), and 2′,3′‐cyclic‐nucleotide 3′‐phosphodiesterase (CNP) were identified in an unbiased manner among the long‐lived proteins of the brain (Toyama et al, 2013).…”
Section: Myelination and Metabolismmentioning
confidence: 99%